Early postmortem brain MRI findings in COVID-19 non-survivors - Coolen, Tim; Lolli, Valentina; Sadeghi, Niloufar; Rovai, Antonin; Trotta, Nicola; Taccone, Fabio Silvio; Creteur, Jacques; Henrard, Sophie; Goffard, Jean-Christophe; Dewitte, Olivier; Naeije, Gilles; Goldman, Serge; et al. (Neurology, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is considered to have potential neuroinvasiveness that might lead to acute brain disorders or contribute to respiratory distress in patients with coronavirus disease 2019 (COVID-19). This study investigates the occurrence of structural brain abnormalities in non-survivors of COVID-19 in a virtopsy framework. In this prospective, monocentric, case series study, consecutive patients who fulfilled the following inclusion criteria benefited from an early postmortem structural brain MRI: death <24 hours, SARS-CoV-2 detection on nasopharyngeal swab specimen, chest CT scan suggestive of COVID-19, absence of known focal brain lesion, and MRI compatibility. Among the 62 patients who died of COVID-19 from March 31, 2020, to April 24, 2020, at our institution, 19 decedents fulfilled the inclusion criteria. Parenchymal brain abnormalities were observed in 4 decedents: subcortical microbleeds and macrobleeds (2 decedents), cortico-subcortical edematous changes evocative of posterior reversible encephalopathy syndrome (PRES; 1 decedent), and nonspecific deep white matter changes (1 decedent). Asymmetric olfactory bulbs were found in 4 other decedents without downstream olfactory tract abnormalities. No brainstem MRI signal abnormality was observed. Postmortem brain MRI demonstrates hemorrhagic and PRES-related brain lesions in non-survivors of COVID-19. SARS-CoV-2-related olfactory impairment seems to be limited to olfactory bulbs. Brainstem MRI findings do not support a brain-related contribution to respiratory distress in COVID-19.